The metastatic potential of canine mammary tumours can be assessed by mRNA expression analysis of connective tissue modulators. (17th November 2011) - Lamp, O.; Honscha, K. U.; Schweizer, S.; Heckmann, A.; Blaschzik, S.; Einspanier, A.
<x xml:space="preserve">Abstract</x> Metastases are the crucial factor for the prognosis of canine mammary tumours (CMTs). In women, the peptide hormone relaxin is linked with metastatic breast cancer. Therefore, the impact of relaxin and its receptors on matrix metalloproteinase (MMP) expression, metastatic disease and survival was analysed using qRT‐PCR and immunohistochemistry of CMT samples from 59 bitches. The expression of relaxin and its receptor RXFP1 (relaxin family peptide receptor 1) was discovered on gene and protein levels. Intratumoural relaxin mRNA expression and relaxin plasma levels had no prognostic value. High mRNA levels RXFP1 were an independent marker of metastatic potential, with a more than 15‐fold risk increase, and a predictor for shorter survival. Also, MMP‐2 expression was associated with early death because of CMT. The mRNA expressions of relaxin, RXFP1 and MMP‐2 were positively correlated indicating a common pathogenetic linkage. Thus, RXFP1 is proposed as a new early marker of metastatic potential in CMT and a possible therapeutic target.